Rancang Bangun Media Pembelajaran Konveyor Sistem SLG Berbasis HMI - Ikhwana Filla; Irwandi; Ar ade jumadil; Irvawansyah; Syahrul Mustafa (Joule (Journal of Electrical Engineering), 2024)
The study intended to create a learning medium tools for sorting systems, elevators, gates based on PLC, and to control systems for sorting objects, freight elevators and gates. The research methods applied to this study are problem identification, toolmaking, design, and testing. Based on tests conducted by the system can detect objects by using proximity infrared sensor by a range of 3 centimetres – 8 centimeter and can be regulated according to need and proximity inductive sensors with a range of 0-4 mm. this media use Infrared sensor range 8 cm and 5 cm while the inductive sensor used by the range 4 mm. Infrared sensors are also used to detect altitude in objects to be sorted. These media control systems are controlled using PLC. Programs for this medium can be created with the language program leadder diagram. For PLC and PC communication using LAN cables. The learning media uses 5 electric motor, three 5 VDC electric motor those are a gate electric motor, a sorting electric motor, and a booster electric motor as well as two 12 VDC electric motor those are conveyor and a freight elevator, so that to connect the SLG learning media to the PLC an additional relay is needed.